Proportion and Factors Predicted Self- Medication in Elderly Population in Yogyakarta - Sari, Andriana; Supadmi, Woro; Perwitasari, Dyah Aryani (Universitas Ahmad Dahlan, 2015)
Pharmacists should give more attention in giving pharmaceutical care services to the elderly patients, because the decrease of physiological function could result more drug related problems. Currently, elderly patients are interesting to do self- medication before visiting the physician. Thus, our study was aimed to understand the proportion of elderly patients who are interesting to do the self-medication and to explore the factors predicted self-medication behavior. This study was carried out by cross-sectional design. Data was collected by doing interview and giving questionnaire to the 544 elderly patients in the pharmacies of YogyakartaProvince which were chosen by proportional area sampling method. Data was analyzed descriptively and using the chi square test to understand factors which could be influenced self medication behavior. Most of the patients choose to do the self medication (63.6%) rather than directly went to the physician (36.4%). There were 3 predictors of self medication behavior in our study, which were occupation, income and type of disease with the RR were; 0.823 (95% CI:0.7010.965), 1.433 (95% CI:1.173-1.751) and 1.027 (95% CI: 1.059-1.376), respectively.The occupation, income and chronic disease could predict of self medication behavior in elderly patients.Keywords: self medication, elderly, predictor